PROHIBITION OF PARALLEL IMPORTS AS A HARD CORE RESTRICTION OF ARTICLE 4 OF BLOCK EXCEPTION REGULATION FOR VERTICAL AGREEMENTS: EUROPEAN LAW AND ECONOMICS - ZEVGOLIS, Nikolaos E.; FOTIS, Panagiotis N. (Journal of Advanced Research in Law and Economics; Vol 2 No 4 (2011): JARLE, Volume II, Issue 2(4), Winter 2011, 2017)
This paper attempts to highlight the main principles of Competition Law (regulatory and case law framework) covering the prohibition of parallel imports and to reveal the main effects of it on the competitive structure of the market. Especially, the regulatory framework relates Block Exception Regulation 330/2010 with Block Exception Regulation 461/2010 in order to determine whether prohibition of parallel imports constitutes a hardcore restriction or not, while the economic analysis evaluates it in a vertical market with few suppliers & buyers which sell goods to the final (domestic) consumers. The results indicate that the prohibition of parallel imports by upstream sellers cause vertical restraints to the domestic customers of the buyers. In any case, this paper focusing mainly on consumer welfare, does not necessarily link parallel imports with the notion of parallel trade and/or parallel exports as well as it does not provide the pros and cons of parallel trade.